1993
DOI: 10.1177/002224299305700104
|View full text |Cite
|
Sign up to set email alerts
|

Control Combinations in Marketing: Conceptual Framework and Empirical Evidence

Abstract: The topic of management control systems has received limited attention in the marketing literature. Though previous research has tended to view each organizational control in isolation, the authors argue that research should examine the simultaneous use of multiple controls. On the basis of previous work, a conceptual framework for combinations of controls is constructed with associated research hypotheses. Four alternative combinations or “systems” of controls are identified: (1) a traditional bureaucratic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
141
1
13

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(160 citation statements)
references
References 29 publications
5
141
1
13
Order By: Relevance
“…These results try to go beyond the traditional studies on organizational control, which have revealed that results and behavior control reduce satisfaction with the control systems and the supervisors (Challagalla and Shervani, 1996). Similarly, Jaworski et al (1993) have demonstrated that the use of bureaucratic controls is associated with a reduction in satisfaction in the personnel subject to such controls. On the other hand, the interactive use of PMSs produces greater motivation to achieve the results thanks to the continual interaction between superiors and e19 subordinates, which allows an informal control, typical of the clan (Ouchi, 1979), to be used alongside the formal controls normally implemented in the analyzed sample.…”
Section: The Interactive Use Of Performance Management System and Thementioning
confidence: 69%
“…These results try to go beyond the traditional studies on organizational control, which have revealed that results and behavior control reduce satisfaction with the control systems and the supervisors (Challagalla and Shervani, 1996). Similarly, Jaworski et al (1993) have demonstrated that the use of bureaucratic controls is associated with a reduction in satisfaction in the personnel subject to such controls. On the other hand, the interactive use of PMSs produces greater motivation to achieve the results thanks to the continual interaction between superiors and e19 subordinates, which allows an informal control, typical of the clan (Ouchi, 1979), to be used alongside the formal controls normally implemented in the analyzed sample.…”
Section: The Interactive Use Of Performance Management System and Thementioning
confidence: 69%
“…Informed by the results of Study 1, three control types were measured: output, process, and normative control. Output control was measured by four items adapted from Jaworski, Stathakopoulos, and Krishnan (1993), which focus on the extent to which standards are set, progress is monitored, and goal attainment is rewarded. Process control and normative control were assessed using the items developed by Sitkin and George (2005).…”
Section: Organizational Controlmentioning
confidence: 99%
“…For example, managers in more rigid and less autonomous situations may perceive role stressors differently. Managers in large organizations are probably influenced by control systems (Jaworski, Stathakopoulos, & Krishnan, 1993); bureaucratic complexity (Fleming, 1966); hierarchical structures (Floyd & Lane, 2000); and other aspects of their organization, which possibly give them a different contextual requirement to perceive stressors. As a result, what a new-business manager may perceive as a challenge stressor, the manager of an established business may perceive as a hindrance stressor.…”
Section: Discussionmentioning
confidence: 99%